In situ fabrication of self-assembled BiOBrxI1−x coated on carbon nanofibers for efficient solar light-driven photocatalytic nitrogen fixation. Issue 12 (5th November 2020) - Hua, Chenghe; Dong, Xiaoli; Zheng, Nan; Zhang, Xinxin; Xue, Mang
Abstract : BiOBr x I1− x composite photocatalysts have been successfully deposited on carbon nanofiber (CNF) substrates via two steps. Abstract : BiOBr x I1− x composite photocatalysts have been successfully deposited on carbon nanofiber (CNF) substrates via two steps. The first step involves an electrospinning technique and the second step includes a one-pot solvothermal method. The characterization results show that a large number of BiOBr x I1− x nanoflowers are deposited on carbon nanofibers, and the diameters of the BiOBr x I1− x /CNF composites are 0.7–1.2 μm. Due to the high electrical conductivity, the CNF could easily capture and transfer electrons, resulting in the effective separation of photoinduced charges. As a result, the BiOBr x I1− x /CNF photocatalysts show a dramatically improved photocatalytic degradation and nitrogen fixation, due to the enhanced light harvesting and effective photoinduced charge separation. Additionally, the increased water oxidation capacity of the BiOBr x I1− x /CNF is also important to enhance the photocatalytic activity. The BiOBr x I1− x /CNF samples also show excellent photochemical stability. This study stresses the significance of the synthesized CNF/semiconductor photocatalysts with high potential for practical applications.